f(R)-Einstein-Palatini formalism and smooth branes - Silva, P. Michel L. T. da [UNESP]; Hoff da Silva, J. M. [UNESP] (Springer, 2017)
In this work, we present the f(R)-Einstein-Palatini formalism in arbitrary dimensions and the study of consistency applied to brane models, the so-called braneworld sum rules. We show that a scenario of thick branes in five dimensions with compact extra dimension in the framework of the f(R)-EinsteinPalatini theory is possible by the accomplishment of an assertive criteria. We finalize investigating the outputs of the resulting sum rules with respect to a stabilization mechanism.